2022
DOI: 10.1111/jre.13002
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiotic relationship between arthritis and the oral‐gut microbiome. A critical review

Abstract: Arthritis and prosthetic joint infections (PJIs) overall are associated with reduced quality of life and limited work capacity. Multiple, overlapping factors contribute to these conditions. Some investigations have suggested a dysbiotic association between the oral‐gut microbiome and pathogenesis of arthritis and PJIs. A better understanding of the role of the oral‐gut microbiota in arthritis and PJI pathophysiology can shed light into how its disequilibrium can discharge a pro‐inflammatory response, and impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Finally, the vascular diffusion of antigens, antibodies and immune complexes to the joints is thought to promote local activation of osteoclasts and low-noise inflammation. 62 Second, these metagenomic studies could eventually reveal a relationship between the oral and intestinal microbiota of gMMP patients, as observed by Imai et al ( 2021) 63 for Crohn's disease. The prospective, controlled study they conducted showed that patients had oral dysbiosis in addition to intestinal dysbiosis, with significant quantitative and qualitative differences in their microbiota compared with control subjects.…”
Section: Our Bicentric Study Nonetheless Presents Certain Limitationsmentioning
confidence: 83%
See 3 more Smart Citations
“…Finally, the vascular diffusion of antigens, antibodies and immune complexes to the joints is thought to promote local activation of osteoclasts and low-noise inflammation. 62 Second, these metagenomic studies could eventually reveal a relationship between the oral and intestinal microbiota of gMMP patients, as observed by Imai et al ( 2021) 63 for Crohn's disease. The prospective, controlled study they conducted showed that patients had oral dysbiosis in addition to intestinal dysbiosis, with significant quantitative and qualitative differences in their microbiota compared with control subjects.…”
Section: Our Bicentric Study Nonetheless Presents Certain Limitationsmentioning
confidence: 83%
“…Research into the existence of a link between periodontitis and other autoimmune inflammatory diseases makes this approach relevant. For example, in rheumatoid arthritis, clinical studies have shown that the oral microbiota of patients, compared with controls, was enriched in periodontopathogenic pathogens, including Porphyromonas gingivalis 62 . This bacterium is thought to be able of inducing joint changes during the preclinical inflammatory phase via one of its virulence factors, peptidylarginine desiminase (PAD), which converts the arginine associated with a peptide into peptidylcitrulline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, P. gingivalis and Fusobacterium nucleatum are the most well-known pathogens of periodontal disease that influence and disturb the structure of the intestinal microbiota community, actively participate in the destruction of the intestinal barrier by increasing the permeability of the intestinal mucus and implicitly in the systemic inflammatory response [29]. Recent studies have shown that dysbiosis in periodontal disease was directly correlated in the long term with RA and when RA was properly treated, oral microbiota dysbiosis was restored [30].…”
Section: The Oral Dysbiosis In Dental Caries Periodontal Disease Oral...mentioning
confidence: 99%